Fly by night : a novel - Larsen, Ward (Oceanview Pub., 2011)
A top-secret drone crashes in the Horn of Africa and prized aircraft ends up in the hanger of a company named Fly by Night Aviation. Jammer Davis is called to investigate a plane a plane crash in the Sudan and discovers a conspiracy that will threaten America like nothing before.